3D simulation of a ballistic direct injection cycle for the assessment of fuel property effects on cavitating injector internal flow dynamics and primary breakup. (15th January 2022) - Schwarz, Philip; Blume, Martin; Weiß, Lukas; Wensing, Michael; Skoda, Romuald
Abstract: The fuel property effect on a high-pressure ballistic injection cycle is studied by n -dodecane and n -heptane because these pure fuels have well-known and well-specified properties. Distinct differences between both fuels are worked out for a ballistic injection cycle by dynamic 3D flow simulations. A two-phase volume of fluid Euler–Euler method for gas mixture is utilized to capture both cavitation and primary breakup in a seamless simulation of injector internal flow and near-nozzle spray. The split-off of primary ligaments is directly resolved down to the available grid limit in computational grid with about 100 million cells. A large-eddy simulation is employed. The simulation results are complemented by laser-induced fluorescence measurements of the spray's near field. The spray head exhibits a mushroom shape for n -dodecane during the early opening phase, while a more complex and unstable misty initial spray head, which is attributed to lower density and viscosity, is observed for n -heptane. For high needle lift, the intensity of string cavitation is lower for n -dodecane due to its larger density and viscosity. During the opening phase, highly unsteady turbulent vortex and cavitation structures are generated. For n -dodecane, these structures survive far into the closing phase. This behavior is attributed to an inertia effect due to the larger density. This hysteresis is also observed for the ligament velocity, which still increases during the early closing phase. For n -heptane, the hysteresis is much less pronounced and ligament velocities are higher due to the lower density. Highlights: Cavitation and primary breakup are treated simultaneously in a seamless simulation. Effect of in-nozzle flow on subsequent flow physics is illustrated. Shape of spray head is density- and viscosity-dependent. Different structures occur in opening and closing phase (fuel-dependent hysteresis). High fuel density promotes survival of structures from opening into closing phase.